Outcomes in patients undergoing urgent colorectal surgery - Teloken, P.; Spilsbury, Katrina; Levitt, M.; Makin, G.; Salama, P.; Tan, P.; Penter, C.; Platell, C. (John Wiley & Sons, 2014)
Background - Urgent surgery for acute intestinal presentations is generally associated with worse outcomes than elective procedures. This study assessed the outcomes of patients undergoing urgent colorectal surgery. Methods - Patients were identified from a prospective database. Surgery was classified as urgent when performed as soon as possible after resuscitation and usually within 24 h. Outcome measures included 30 days mortality, return to theatre, anastomotic leak and overall survival. Results - Two hundred forty-nine patients were included in the analysis. Median age was 65 years (interquartile range 48–74). The most common presentations were obstruction (52.2%) and perforation (23.6%). Cancer was the disease process responsible for presentation in 47.8% of patients. Thirty-day mortality was 6.8%. Age (odds ratio 1.08 95% confidence interval (CI) 1.02–1.15; P = 0.01), American Society of Anesthesiologists 4 (odds ratio 7.14 95% CI 1.67–30.4; P = 0.008) and cancer (odds ratio 6.61 95% CI 1.53–28.45; P = 0.011) were independent predictors of 30 days mortality. Relaparotomy was required in six (2.4%) cases. A primary anastomosis was performed in 156 (62.6%) patients. Anastomotic leak occurred in four (2.5%) patients. In patients with cancer, overall 5-year survival was 28% (95% CI 19–37), corresponding to 54% (95% CI 35–70) for stages I and II, 50% (95% CI 24–71) for stage III and 6% (95% CI 1–17) for stage IV disease. Urgent surgery was independently associated with worse overall survival (hazard ratio 2.65; 95% CI 1.76–3.99; P < 0.001). Conclusion - In patients undergoing an urgent resection within a colorectal unit, performing a primary anastomosis is feasible and safe in the majority, relaparotomies are required in a minority and urgent surgery is an important predictor of worse prognosis in those with colorectal cancer.